Rethinking the ‘Other’ Border: Caribbean Migration to Canada - Flynn, Karen (Review of International American Studies, 2025)
This paper challenges the myth of Canada as the “Promised Land” for displaced peoples, such as enslaved African Americans who sought refuge via the Underground Railroad. “Drawing on archival and secondary sources, the paper examines the measures taken by Immigration Canada to exclude Caribbean people, arguing that these policies are inextricably connected to the question of who is considered worthy of belonging to and contributing to the nation-building project. While some recognize that Chinese and Sikh immigrant men furnished the physical labor necessary for nation-building by constructing railways and working in the lumber industry, the bodies and the work performed are gendered. This paper seeks to expand the repertoire of actors and the parameters of what counts as nation-building activities by including Caribbean domestic workers. Specifically, the paper examines how these working-class women both inadvertently and directly contributed to Canada’s nation-building in two ways: 1) by assuming reproductive tasks on behalf of middle-class white women and their families and 2) through their activism against deportation.